2018
DOI: 10.1007/s10964-018-0913-7
|View full text |Cite
|
Sign up to set email alerts
|

Who Becomes a Bullying Perpetrator After the Experience of Bullying Victimization? The Moderating Role of Self-esteem

Abstract: It is well known that victims of bullying could become a bullying perpetrator later on. However, there are some cases where victims do not become bullies after being bullied. What constitutes the differences between the two groups, who show different response strategies despite the similar experiences of victimization, is the main question that the current study poses. Based on the threatened egotism theory, the current longitudinal study postulates that there could be possible moderating effects of self-estee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 34 publications
1
31
1
1
Order By: Relevance
“…In relation to the second finding, self-esteem was not found to mediate cyberbullying victimization and perpetration which contradicts several previous literatures which contend that low self-esteem levels predict cyberbullying [18], [20] in addition to a study which relates high self-esteem levels with cyberbullying [22]. Therefore, the finding of this study only aligns with [21] where low levels of self-esteem do not predict cyberbullying perpetration and victimization.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…In relation to the second finding, self-esteem was not found to mediate cyberbullying victimization and perpetration which contradicts several previous literatures which contend that low self-esteem levels predict cyberbullying [18], [20] in addition to a study which relates high self-esteem levels with cyberbullying [22]. Therefore, the finding of this study only aligns with [21] where low levels of self-esteem do not predict cyberbullying perpetration and victimization.…”
Section: Discussioncontrasting
confidence: 98%
“…However, a study [21] found low self-esteem levels did not produce a predictive factor for cyberbullying victimization and perpetration. Another study which further expounds the complicated relationship between self-esteem and cyberbullying is where they wrote that students with high levels of self-esteem predicted bullying perpetration when being bullied while students with lower self-esteem reported lower probability in bullying perpetration [22]. Therefore, there exist multiple discrepancies on the topic hence necessitating the current study.…”
Section: Introductionmentioning
confidence: 97%
“…It is suggested that the switch from one role to another is particularly specific for students with high self-esteem. Another longitudinal study revealed that “students with higher self-esteem were the most likely to engage in future bullying perpetration in response to bullying victimization, while the students with lower self-esteem were the least likely to engage in future bullying perpetration”; as such, for the bully victims with high self-esteem it serves as a possible way to recover threatened egotism (Choi and Park, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the moderating role of self-concept in the mediating effect of loneliness on personality traits and bullying/being bullied, constructing comfortable school atmospheres (Xie and Mei, 2019) and perfecting personality educations (Miao, 2019) may overcome the negative impacts of school bullying. To be specific, first, education departments should offer targeted psychological guidance according to the different personality characteristics of teenagers, such as counseling for bullies with low self-esteem, paying attention to vulnerable victims with high self-esteem (Choi and Park, 2018), and preventing bullying by those with defensive personalities. Second, mental health courses on cultivating a healthy personality should be offered to teenagers.…”
Section: Moderated Role Of Middle School Students' Self-conceptmentioning
confidence: 99%